Effects of whole-body cryostimulation on spinal and shoulder range of motion in individuals with obesity - Cerfoglio, Serena; Verme, Federica; Fontana, Jacopo Maria; Alito, Angelo; Galli, Manuela; Capodaglio, Paolo; Cimolin, Veronica (Frontiers in Rehabilitation Sciences, 2025)
IntroductionFlexibility and mobility are essential components of physical fitness, impacting joint function and musculoskeletal health. Individuals with obesity often exhibit restricted range of motion (ROM), exacerbated by muscle weakness, joint stiffness, and altered posture. Whole-body cryostimulation (WBC), involving exposure to low temperatures, has shown promise in alleviating inflammation and improving physical performance. This study evaluates the acute and short-term effects of WBC combined with rehabilitation on spinal and shoulder ROM in individuals with obesity.MethodsThis non-randomized controlled trial included 42 adults with obesity undergoing a 4-week multidisciplinary rehabilitation program consisting of nutritional intervention, psychological support, physiotherapy, and physical activity. Participants were divided into two groups: a WBC group [WG, n = 21; 12 males (BMI = 38.77 kg/m2), 9 females (BMI = 38.45 kg/m2)] receiving 10 sessions (−110°C, 2 min/session) alongside rehabilitation, and a control group [CG, n = 21; 12 males (BMI = 43.37 kg/m2), 9 females (BMI = 41.86 kg/m2)] receiving rehabilitation alone. ROM for spine-related (i.e., anterior flexion, lateral bending, rotation) and shoulder-related (i.e., frontal rise, lateral rise, backward push) motor tasks was assessed at different time-points using a marker-based optoelectronic motion capture (MoCap) system. Repeated-measures (RM-ANOVA) analyzed changes within groups over time, post hoc t-tests identified significant effects, and mixed RM-ANOVA compared changes between groups.ResultsExcept for anterior flexion, WG showed significant improvements (p < 0.05) in ROM and task duration across all movements, with moderate to large effect sizes (0.20 ≤ d < 0.80). For instance, improvements were reported for ROM in shoulder flexion (acute-post: p = 0.045, d = 0.43) and extension (pre-post: p < 0.001, d = 0.51), as well as for spinal rotation (pre-post: p = 0.029, d = 0.42). Similarly, task duration reductions across all tasks, such as spinal rotation (pre-post: p = 0.040, d = 0.45) and lateral bending (pre-post: p < 0.025, d = 0.54). Conversely, CG showed no significant ROM changes.DiscussionWBC, when combined with rehabilitation, led to significant improvements in spinal and shoulder ROM. Acute and short-term benefits were observed in ROM and task duration, supporting WBC as a valuable addition to rehabilitation for individuals with obesity. Clinical Trial Registrationhttps://clinicaltrials.gov/study/NCT05443100, identifier NCT05443100.